Pengaruh Promosi Jabatan, Pendidikan, Dan Masa Kerja Terhadap Kinerja Pegawai Pada Dinas Koperasi, Perindustrian, Dan Perdagangan Kota Malang - Ameirul Widiananda; Abdul Kodir Djaelani; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of promotion on employee performance, the influence of position on employee performance, and the influence of tenure on employee performance. This research is a type of explanatory research. The research subjects were carried out on employees of the Cooperative Office. Industry and Trade in Malang City with 56 employees as respondents. With the Criteria Respondents are Employees with TPOK (Supporting Operational Activities) and PTT (Non-permanent Employees) status. Data collection method is done by using a questionnaire. The analytical method used is multiple linear regression analysis. The results showed that the promotion had an effect on employee performance, education had an influence on employee performance, and tenure had an effect on employee performance. Likewise with the variable promotion of position, education, and years of service simultaneously affect the performance of employees.Keywords : promotion, education, tenure, employee performance.